2022
DOI: 10.23736/s2724-6329.21.04478-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ankylosed deciduous molars with or without permanent successors in children and adolescents: a systematic review

Abstract: HTML PDF Materiale_supplementareINTRODUCTION: The aim of this systematic review was to provide guidelines for decision-making during orthodontic treatment planning of infra-occluded deciduous molars with or without their successors in children and adolescents. EVIDENCE ACQUISITION: Computerized search was conducted on Medline via PubMed, and Cochrane Library. Articles published until 2020 in English language were analyzed following the Preferred Reporting Items for Systematic Reviews (PRISMA) Checklist. Observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In contrast, Savoldi et al found no statistically significant change in the position of the hyoid bone, as well as in the size of the airway, in patients treated with Herbst compared with a group treated with high traction [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Savoldi et al found no statistically significant change in the position of the hyoid bone, as well as in the size of the airway, in patients treated with Herbst compared with a group treated with high traction [ 66 ].…”
Section: Discussionmentioning
confidence: 99%